Mobile Outreach Services as a Strategy for Inclusive Population Administration in Archipelagic Regions: A Literature Review - Ivana Beatrice Manpioper; Amirul Mustofa; Sedarmayanti Sedarmayanti; Dian Ferriswara (International Journal of Humanities and Social Sciences Reviews, 2026)
Unequal access to population administration services remains a persistent governance challenge in archipelagic and geographically constrained areas, where spatial dispersion, limited connectivity, and high mobility costs systematically hinder citizens’ ability to obtain legal identity documents. In island regions, weak sea transportation networks, weather-dependent travel, and long distances to administrative centers reduce the feasibility of conventional, office-based service delivery, producing administrative exclusion that undermines equal citizenship. These barriers also intersect with socio-administrative realities, including the prevalence of unregistered marriages (nikah sirri), which constrains civil registration processes and delays the formal recognition of marital status and household composition within population administration systems. Against this backdrop, this review article aims to synthesize reputable scholarly literature on pelayanan jemput bola (mobile/outreach public services) as a policy strategy to advance service inclusivity and administrative justice in population administration, particularly for geographically marginalized communities. Methodologically, the article employs a thematic–conceptual literature review, systematically identifying and analyzing peer-reviewed journal articles and conference proceedings published primarily within the last five to ten years across recognized academic databases. The synthesis identifies key rationales and conceptualizations of outreach services, maps major implementation models (mobile units, community-based outreach, integrated one-stop outreach, and hybrid outreach–digital arrangements), and consolidates recurrent success factors, including local state capacity, inter-actor coordination, frontline discretion, and policy support. It also highlights persistent challenges such as logistical uncertainty, resource constraints, uneven digital readiness, and governance fragmentation across island territories. The article concludes that mobile/outreach population administration services can substantially improve equitable access to legal identity and strengthen civil rights realization in archipelagic contexts, but only when embedded in capacity-building and geography-sensitive governance arrangements. By integrating fragmented strands of scholarship, the review offers a conceptually grounded framework and policy-relevant implications for designing sustainable and just population administration reforms in island regions.